Effect of genotype on the hematological parameter of TETRA-SL and Hungarian Partridge coloured chickens at young age - Lugata, James Kachungwa; Ozsváth, Xénia Erika; Ndunguru, Sawadi Fransisco; Kidane, Gebrehewaria Reda; Knop, Renáta; Angyal , Eszter; Oláh, János; Szabó, Csaba (Acta Agraria Debreceniensis, 2022)
Indigenous chickens are well known for their dual-purpose function and palatable meat. However, the information on their hematology parameters is lacking and hence hampering the poultry industry production of local breeds. The main objective of this study was to examine the hematological parameters of Hungarian Partridge Coloured hen (HPC) and TETRA-SL (TSL) genotype and determine the hematological reference interval values. This trial was part of the larger experiment where a total of 200 chicks (HPC + TSL) were reared. For this trial the blood samples were obtained from brachial wing veins of 8 chicks of each genotype for blood hematological analysis. The results indicated that some of the hematological parameters such as red blood cells-RBC, white blood cells-WBC, hemoglobin-Hb, hematocrit-Ht, platelets-Plt, lymphocytes-LYM, and granulocytes-GRAN were significantly affected by the genotypes (p < 0.05). The genotype did not affect the mean corpuscular volume-MCV, mean corpuscular hemoglobin-MCH, mean corpuscular hemoglobin concentration-MCHC, and GRAN (p > 0.05). The hematological reference interval values were slightly higher in the TSL genotype compared to HPC chicks. It is concluded that genotype has a significant effect on the hematological parameters. The results from this trial will be help and design the baseline reference values for the HPC genotype which will be useful in assessing the health status of these indigenous chickens.